Comparison of various electrode fabrication methods for use in an electrolyzer to produce of HCl and NaOH from NaCl - Kim Jaewon; Saleem Abbas; Ki Bong Lee; Ha, Heung Yong (The Electrochemical Society, 2020)
Many researches on CO2 capture and utilization (CCU) are being actively pursued to suppress its global warming effects and to utilize CO2 as a feedstock for producing useful organic and inorganic substances such as methanol, formic acid, and carbonates through biological, thermal, photochemical and electrochemical methods. This study focuses on the fabrication methods of anodes for use in an electrolyzer to produce alkali (NaOH) and hydrochloric acid (HCl) by splitting a brine (aqueous NaCl) that would be used to convert carbon dioxide into carbonate minerals at a subsequent stage. The electrolyzer consists of an anode, a membrane 1, a middle plate, a membrane 2 and a cathode. A hydrogen gas is supplied to the anode compartment, a dilute NaOH aqueous solution is to the cathode, and a feed solution of NaCl is to the middle plate. The membranes can be both cationic ones. Upon applying a voltage of around 1.5V, HCl is produced at the anode, and NaOH is produced at the cathode. This study is focused on the fabrication methods to make active and durable anodes. The anode is usually made of Pt particles dispersed on porous and electrically conductive substrates. The fabrication methods can be appropriately chosen depending on the types of substrates. In this study, two types of substrates were used, carbon cloth and carbon paper. In case of using a carbon cloth as substrate, two types of fabrication methods were used, a spraying method and a screen printing method while in case of using a carbon paper an electroplating method was used. When using a spraying method, an appropriate amount Pt/C catalyst powder was dispersed in an aqueous isopropyl alcohol(IPA) solution containing a given amount of Nafion ionomer to make a catalyst ink. The catalyst ink was sprayed on a carbon cloth using a nitrogen spray gun to make an anode consisting a Pt-catalyst coated a carbon cloth having a thickness of 0.45 mm. After drying in an oven, it was used as anode for the electrolyzer. In the case of screen printing method, a viscous catalyst slurry was made by mixing an appropriate amount of catalyst powder, IPA, Nafion ionomer and glycerin, which was then spread on the surface of a carbon cloth (CC) using a silk screen having a proper mesh size. The resulting slurry-coated CC was put in a vacuum oven at 150oC to remove the glycerin, followed by a pretreatment step to swell the dried ionomer in the catalyst layer. The Pt loading was 0.30 mg/cm2. The electroplating method was used to plate Pt on the surface of a carbon paper (CP) having a thickness of 0.20mm. The CP was first pre-treated in a H2SO4 solution and then immersed in a plating solution consisting of H2PtCl6 in a 0.5M solution. Electroplating of Pt was carried out by applying a current of 20 mA/cm2 to deposit 0.30mg-Pt/cm2. Those fabricated anodes were installed in an electrolyzer cell using Nafion 115 as membrane 1 and 2 and a Ni mesh electrode as cathode. The cell performance was measured by supplying H2 into the anode side and a dilute NaOH solution into the cathode side while applying a voltage of 1.5V to the cell. As shown in the figure, the cell performances vary depending on the anode fabrication methods, indicating the structure of anode affects the cell performance. Therefore, in order to improve the performance of the anodes, various fabrication factors need to be optimized to make the structure of the catalyst layer suitable for the reaction.
Keywords: Electrolysis; NaCl; electrode; operating condition